1998
DOI: 10.1002/(sici)1096-9926(199806)57:6<310::aid-tera4>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Rat embryos cultured under copper‐deficient conditions develop abnormally and are characterized by an impaired oxidant defense system

Abstract: Rat embryos (gestation days 9.0 and 10.0) obtained from dams that were fed a Cu-adequate (8 micrograms Cu/g) or Cu-deficient (< 0.5 micrograms Cu/g diet were cultured for 48 hr in Cu-adequate (16.2 microM) or Cu-deficient (1.0 microM) rat serum. Control embryos cultured in control serum were morphologically normal. Embryos from Cu-deficient dams developed abnormally when cultured in Cu-deficient serum; the abnormalities included distended hindbrains, blisters, blood pooling, and cardiac defects. Control embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Zinc, in addition, can protect the embryo from damage caused by other teratogenic agents, though zinc deficiency in the mother may be harmful to the embryo (Jankowski et al 1995). In an experimental rat embryo culture system, abnormal development could also be induced under copper-deficient conditions which were associated with an impaired oxidant defense system (Hawk et al 1998). Information on the teratogenic effects of vanadium have mainly been obtained from various animal test systems, "but vanadium appears to be only slightly teratogenic, if at all" Gerber 1994, Domingo 1996).…”
Section: Teratogenicitymentioning
confidence: 72%
“…Zinc, in addition, can protect the embryo from damage caused by other teratogenic agents, though zinc deficiency in the mother may be harmful to the embryo (Jankowski et al 1995). In an experimental rat embryo culture system, abnormal development could also be induced under copper-deficient conditions which were associated with an impaired oxidant defense system (Hawk et al 1998). Information on the teratogenic effects of vanadium have mainly been obtained from various animal test systems, "but vanadium appears to be only slightly teratogenic, if at all" Gerber 1994, Domingo 1996).…”
Section: Teratogenicitymentioning
confidence: 72%
“…However, in both the in vivo and in vitro experiments, Cu-deficient embryos were smaller than controls as assessed by head and crown-rump lengths. Consistent with our previous report [4], the control embryos in vivo taken on GD 12 were morphologically similar to the in vitro controls. We observed a small number of abnormalities in the in vivo Cu-FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the developmental outcome of the Cu-deficient embryos from the in vivo and in vitro studies may be caused by the teratogenic nature of culture sera, which was more severely depleted in Cu (0.9 M) than in the sera to which the embryos were exposed in utero (ഠ5.0 M). We have shown that when Cu-deficient embryos are cultured in Cudeficient culture media that has been repleted with Cu or are cultured in serum from Cu-adequate animals, the embryonic malformations are decreased [4,31]. These data demonstrate the sensitivity of postimplantation rat embryos to changes in culture Cu concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations